The Joseph story between Egypt and Israel - Römer, Thomas (Archaeology and bible, 2021)
Die Josephsgeschichte dient in ihrer Stellung zwischen Erzvätern und Exodus dazu, eine Erklärung dafür zu bieten, wie Jakob und seine Familie nach Ägypten kamen. Außerhalb der Tora wird sie allerdings kaum erwähnt. Sie scheint zunächst für sich entstanden zu sein, doch wann, wo und weshalb ist sie geschrieben worden? Dieser Band bringt Vertreterinnen und Vertreter der Bibelwissenschaft und der Ägyptologie zusammen, um diese Fragen einer Klärung zuzuführen.InhaltsübersichtFranziska Ede: The Joseph Story: Diaspora Novella-Patriarchal Story-Exodus Narrative (Part I) − Reinhard Kratz: The Joseph Story: Diaspora Novella-Patriarchal Story-Exodus Narrative (Part II) − Thomas Römer: How »Persian« or »Hellenistic« is the Joseph Narrative? − Lauren Monroe: Stripping off the Robe: New Light on »Joseph the Hebrew« and the bet-yosef − Samuel Arnet: Aspects of Jewish Identity in the Joseph Story − Safwat Marzouk: Forced Migration and Reconciliation in the Joseph Narrative − Konrad Schmid: Sapiential Anthropology in the Joseph Story − Camille Guérin: The Joseph Story from an Egyptological Perspective − Bernd Schipper: Joseph in Egypt: A Critical Evaluation of the Classical Parallels and a New Interpretation